lsotopic and Palynological Records of the Late Pleistocene in Eastern Canada and Adjacent Ocean Basins - Hillaire-Marcel, Claude; de Vernal, Anne (Géographie physique et Quaternaire, 1989)
ABSTRACTCorrelations of isotopic and palynological records from deep sea cores in Baffin Bay and Labrador Sea with terrestrial palynological sequences, supported by a few Th/U chronological controls, allow the establishment of a regional climatostratigraphic scheme for the Late Pleistocene climatic fluctuations in eastern Canada. During the climatic optimum of isotopic substage 5e, warmer conditions than present prevailed both on land and in oceanic surface water masses. The 5e/5d transition is marked by an abrupt shift in 818O values in Baffin Bay and Labrador Sea as a consequence of ice growth over circumpolar areas of northeastern Canada. From substage 5d to substage 5a, the Baffin Bay border lands experienced glacial conditions while subarctic to cool-temperate and humid climates persisted over Labrador Sea and Atlantic Canada. A short (<104yrs) stage 4 is recorded in deep sea cores with high 8'8O values. It corresponds to the Early Wisconsinan southward extension of the Laurentide Ice Sheet dated at ca. 80,000 yrs in the central St. Lawrence Lowland. There is no clear evidence of full glacial conditions in the Atlantic Provinces during this episode. Stage 3 (Middle Wisconsinan) corresponds in the isotopic records to large oscillations in 818O values suggesting meltwater transits in both Baffin Bay and Labrador Sea. The ice cover remained relatively extensive over eastern Canada, although some areas experienced ice-marginal conditions : in the Atlantic Provinces, notably on Cape Breton Island, hemiarctic to subarctic climate is inferred from palynological records; in the Appalachian foothills of Québec glacial Lake Gayhurst developed some 46,000 yrs ago. During isotopic stage 2 (Late Wisconsinan), the Laurentide Ice Sheet reached its maximum extent while satellitic ice-caps developed over the Atlantic Provinces. In deep sea cores, high 818O values mark the full glacial conditions of isotopic stage 2, although slightly lower values in western Labrador Sea indicate discrete but continuous meltwater influxes. An early melting phase of the northeastern margin of the Laurentide Ice Sheet is recorded shortly after 16,700BP. The full ice-retreat is observed after ca. 11,000BP. At that time, southeastern Canada was already largely ice-free. Finally, the optimum climatic conditions of isotopic stage 1 settled diachronously in the adjacent basins of eastern Canada.